Multiphase solid inclusions in ultrahigh-pressure metamorphic rocks: A snapshot of anatectic melts during continental collision. (1st September 2017) - Gao, Xiao-Ying; Chen, Yi-Xiang; Zhang, Qiang-Qiang
Graphical abstract: Highlights: Silicate and carbonate MS inclusions were found in garnet from UHP metamorphic rocks. The MS inclusion represent the crystallization products of dehydration melting of hydrous minerals. The MS inclusions provide important records of partial melting and melt evolution in collisional orogens. Abstract: Partial melting of crustal rocks may take place during continental collision, giving rise to anatectic melts. Their composition and evolution are major concerns in the chemical geodynamics of continental subduction zones. They are often recorded by multiphase solid (MS) inclusions enclosed by peritectic minerals in ultrahigh-pressure (UHP) metamorphic terranes inside collisional orogens. These MS inclusions generally show negative crystal shapes with the wedge-shaped off-shoot structure in garnet, omphacite and kyanite. They contain a number of silicate, carbonate and sulfate minerals such as K-feldspar, plagioclase, quartz, epidote, calcite and barite, with occasional occurrences of magnetite, zircon and pyrite. An integrated study of petrology, mineralogy and geochemistry indicates that the MS inclusions are the primary crystallization product of former silicate and carbonate melts. The silicate melts were derived from dehydration melting of hydrous minerals such as phengite and paragonite in UHP metamorphic rocks, and the carbonate melts were produced by partial melting of subducted carbonate minerals. Some MS inclusions show remarkably high Na contents, suggesting their derivation from dehydration melting of paragonite. In contrast, K-bearing MS inclusions are produced by dehydration melting of K-bearing hydrous minerals like phengite. Many studies have been devoted to the mineralogical and geochemical compositions of MS inclusions in UHP metamorphic rocks, with the aim to determine the time and mechanism of crustal anataxis during collisional orogeny. Various analytical methods were used to characterize the morphology, texture, mineral chemistry and trace element composition of MS inclusions. The results provide insights into the physicochemical properties of anatectic melts in continental subduction zones. The partial melting of deeply subducted crustal rocks would lead to their significant differentiation in lithochemistry and geochemistry. This process has great bearing on the tectonothermal evolution of continental subduction zones and the exhumation mechanism of deeply subducted crustal slices.